THE INFLUENCE OF INTELLECTUAL CAPITAL AND NON PERFORMING FINANCING TO THE FINANCIAL PERFORMANCE OF SHARIA BANKING IN INDONESIA - Khoirunnisa Azzahra (Universitas Putera Batam, 2020)
The development of Islamic banking finance has not met OJK's expectations, which is still below 5%. This reseach purposes to analyze the effect of intellectual capital and non-performing financing on financial performance. The research method used is descriptive quantitative using multiple linear regression test models. Withdrawal of samples using purposive sampling method in order to obtain 6 Islamic commercial banks in Indonesia with the data studied as many as 30 data used as research samples and hypothesis testing is done using partial significant test (t test) and simultaneous significant test (F test) with ɑ = 5%. Hypothesis test results show that intellectual capital and non-performing financing have a significant effect on financial performance, either partially or simultaneously.